Unveiling COVID-19’s Influence on Diet-Related Lifestyle: Insights from Google Trends Query Volumes - Michael, Patricia; Shivshetty, Nagaveni; Mukherjee, Jyoti; Poosarla, Venkata Giridhar; Oli, Ajay Kumar (Current Nutrition & Food Science, 2025)
AimThis study aimed to showcase the particular lifestyle and behavioural pattern changes during the pandemic using Google Trends (GT).BackgroundThe pandemic hit by the Coronavirus Disease 2019 (COVID-19) globally has brought basic living into the context of surprise. Since the lockdown and social restrictions, the population has faced many changes in their daily routine.ObjectiveThe purpose of the study was to demonstrate how COVID-19 has affected eating habits and lifestyle in India.MethodsA retrospective analysis was carried out with the aid of Google Trend Relative Search Volume (RSV) data obtained for interest areas, such as COVID-19 cases, symptoms, preference of medicines, choice of nutrients, reduced physical activity, and watching varied Over-the-top media service (OTT) platforms as the source of entertainment; these were the variables that were taken into consideration to derive correlation coefficient values.ResultsThere was a strong positive correlation found between zinc and vitamin C, zinc and vitamin D, and vitamin C and D, which was 0.83, 0.78, and 0.72, respectively. Symmetrical observation has been observed in Netflix and Amazon Prime as 0.81; a notable negative correlation was found between COVID-19 and gym as -0.32.ConclusionThis study can be used as a checkpoint list for future predictions and past timelines and how they have a cohabitant role in the spread of the epidemic and its line of mitigation strategies.
Keywords: sedentary lifestyle